Differences in the neurocognitive profiles of professional and semi-professional male South African rugby union players. Issue 2 (4th March 2019) - Kruger, Ankebé; Du Plooy, Kobus; Kruger, Pieter
Abstract : This study investigated possible cognitive functioning profile differences between professional and semi-professional rugby players. Seventy-nine male rugby union players (professional = 55, semi-professional = 24; age range = 19–37 years) participated in the study. The players completed a battery of neuropsychological functioning tests covering the following domains: memory tasks, attention and behavioural tasks, sensory-motor tasks, executive functioning tasks, verbal tasks, and emotion identification tasks. Results following Fisher's exact test comparisons revealed no significant group differences in the cognitive functioning profiles.